On the Expressive Power of Extended Process Rewrite Systems - Kretínský, Mojmír; Rehák, Vojtech; Strejcek, Jan (BRICS Report Series, 2004)
We provide a unified view on three extensions of Process rewrite systems (PRS) and compare their and PRS’s expressive power. We show that the class of Petri Nets is less expressible up to bisimulation than the class of Process Algebra extended with finite state control unit. Further we show our main result that the reachability problem for PRS extended with a so called weak finite state unit is decidable.